Borrelia burgdorferi BBI39 Paralogs, Targets of Protective Immunity, Reduce Pathogen Persistence Either in Hosts or in the Vector. (31st January 2017) - Singh, Preeti; Verma, Deepshikha; Backstedt, Brian T.; Kaur, Simarjot; Kumar, Manish; Smith, Alexis A.; Sharma, Kavita; Yang, Xiuli; Azevedo, José F.; Gomes-Solecki, Maria; Buyuktanir, Ozlem; Pal, Utpal
Abstract: Borrelia burgdorferi genome harbors several paralogous gene families (pgf) that can encode immunogenic proteins of unknown function. Protein–protein interaction assays using a transmission-blocking vaccine candidate, BBA52, as bait identified an interacting partner in spirochetes—a member of pgf 54, annotated as BBI39. We show that BBI39 is a surface-exposed membrane antigen that is immunogenic during spirochete infection, despite the gene being primarily transcribed in the vector with a transient expression in the host only at tick-bite sites. Immunization of rodents with BBI39, or a diverse paralog, BBI36, or their combination impaired pathogen acquisition by the vector, transmission from ticks to hosts, or induction of disease. High-titer BBI39 immunoglobulin G antibodies, which have borreliacidal properties, could be generated through routine subcutaneous or oral immunization, further highlighting use of BBI39 proteins as novel Lyme disease vaccines that can target pathogens in the host or in ticks.